Gestión del talento humano y su incidencia en el desempeño laboral, en los locales de venta Dyanita, cantón Guaranda, provincia Bolívar, año 2024 - Pilamunga Guapisaca, Andrés Paul (2025)
The present investigation called Human Talent Management and its impact on Work Performance, in the Dyanita sales premises, Guaranda canton, Bolívar province, year 2024. Its objective is to determine how Human Talent Management affects the work performance of employees. workers in the “DYANITA” sales premises, based on the information that will be obtained, it will be possible to know the real situation of the organization. Through this, it will allow us to raise a problem and provide a solution to it, in this way we will know in depth that human talent management has become a fundamental basis of every company since through it the interests of employees can be understood, understood and managed. The qualitative approach is a methodology that is used to carry out direct observation, interviews and by using the collection of information it will allow us to understand the different opinions and definitions. Finally, it is concluded that human talent today is the most valuable resource of a company since through it not only improves job performance, but also helps meet the company's objectives. To achieve this, it is necessary to implement multiple aspects such as recruitment, selection, training, incentives, among others, to ensure that employees perform their duties excellently